Modeling the Formation of Attentive Publics in Social Media: The Case of Donald Trump. Issue 2 (3rd March 2020) - Wells, Chris; Zhang, Yini; Lukito, Josephine; Pevehouse, Jon C. W.
Abstract : Previous research has shown the importance of Donald Trump's Twitter activity, and that of his Twitter following, in spreading his message during the primary and general election campaigns of 2015–2016. However, we know little about how the publics who followed Trump and amplified his messages took shape. We take this case as an opportunity to theorize and test questions about the assembly of what we call "attentive publics" in social media. We situate our study in the context of current discussions of audience formation, attention flow, and hybridity in the United States' political media system. From this we derive propositions concerning how attentive publics aggregate around a particular object, in this case Trump himself, which we test using time series modeling. We also present an exploration of the possible role of automated accounts in these processes. Our results reiterate the media hybridity described by others, while emphasizing the importance of news media coverage in building social media attentive publics.